The role of education on sustainable human development in Iraq, an analytical study for the period 2003-2020 (Texas Journal of Multidisciplinary Studies, 2023)
The Sustainable National Development Plan 2030 included seventeen development goals called the Sustainable Development Goals, where the education sector is the main goal for achieving sustainable development. Sustainable development is defined as meeting the needs of the present without negatively affecting the ability of future generations to meet the needs of the future. Education is considered to play a major role in the required transformation into more sustainable societies, from an environmental point of view, and in coordination with government initiatives, civil society initiatives, and the private sector, education also contributes to the development of skills, concepts, and tools that can be used to reduce or stop unsustainable practices. Sustainable, including the excessive consumption of resources and the acceleration of the erosion of the knowledge of the indigenous people and their ways of living that are environmentally sustainable. Therefore, it may require adapting and transforming education to ensure its positive impact